Albizia harveyi: phytochemical profiling, antioxidant, antidiabetic and hepatoprotective activities of the bark extract - Sobeh, Mansour; Mahmoud, Mona Fouad; Abdelfattah, Mohamed A. O.; El-Beshbishy, Hesham A.; El-Shazly, Assem; Wink, Michael (Medicinal chemistry research, 2017)
Profiling the polyphenols in the methanol extract from the bark of Albizia harveyi was performed by HPLC-PDA-ESI-MS/MS analysis. The phytochemical analysis identified 39 compounds, the majority of them were flavan-3-ol derivatives and condensed tannins. Total phenolic content, determined by the Folin-Ciocalteu method amounted to 489 mg gallic acid equivalents/g extract. The extract showed promising antioxidant activities with an EC50 of 3.6 µg/mL and 18.32 mM FeSO4 equivalent/mg extract in radical scavenging assay and ferric reducing antioxidant power assays, respectively. The hepatoprotective potential of the extract in rats was determined in vivo in a d-galactosamine-induced liver toxicity model. A dose of 100 mg/kg (body weight) of the bark extract reduced levels of aspartate aminotransferase, gamma-glutamyltransferase and total bilirubin by 35.7, 65.3, and 23.8% (p < 0.05), respectively whereas glutathione was increased by 59.1%. These effects were similar to silymarin which was used as positive control. The extract (100 mg/kg (body weight) mediated a substantial antidiabetic response in streptozotocin-induced diabetic rats manifested by a significant reduction in serum glucose and lipid peroxides and significant increase of serum insulin. Docking of d-(+) catechin and the dimer (epi)catechin-(epi)catechin into the active site of the enzymes human pancreatic α-amylase, maltase-glucoamylase, and aldol reductase revealed that these enzymes may be possible targets via which, the studied Albizia harveyi extract could exert its antidiabetic effect.